The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/ijnp/pyac016
|View full text |Cite
|
Sign up to set email alerts
|

High S100B Levels Predict Antidepressant Response in Patients With Major Depression Even When Considering Inflammatory and Metabolic Markers

Abstract: Background The relationship between antidepressant response and glial, inflammatory, and metabolic markers is poorly understood in depression. This study assessed the ability of biological markers to predict antidepressant response in major depressive disorder (MDD). Methods We included 31 MDD outpatients treated with escitalopram or sertraline for 8 consecutive weeks. The Montgomery-Asberg Depression Rating Scale (MADRS) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In the study by Navines et al (2022), patients with high baseline S100B levels significantly improved Montgomery Åsberg Depression Rating Scale scores compared to those with low S100B levels during pharmacotherapy with escitalopram or sertraline [ 79 ]. No correlation of S100B with ketamine treatment of drug-resistant depression was found [ 80 , 81 ], nor correlation with suicidal ideation in ketamine-treated patients [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Navines et al (2022), patients with high baseline S100B levels significantly improved Montgomery Åsberg Depression Rating Scale scores compared to those with low S100B levels during pharmacotherapy with escitalopram or sertraline [ 79 ]. No correlation of S100B with ketamine treatment of drug-resistant depression was found [ 80 , 81 ], nor correlation with suicidal ideation in ketamine-treated patients [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies reported a lack of correlation of S100B levels with symptoms severity using different clinical scales: Hamilton Depression Rating Scale (HDRS) [ 59 , 60 , 62 , 65 , 72 , 73 , 74 , 77 , 78 ], Clinical Global Impression (CGI), Mini-Mental State Examination (MMSE) [ 72 ]. Quick Inventory of Depressive Symptomatology Self-Report (QIDS-SR) [ 82 ], Beck Depression Inventory (BDI) [ 61 ], Hamilton Anxiety Scale (HAMA) scores [ 59 ], and Montgomery Åsberg Depression Rating Scale (MADRS) [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being a highly organized structure and coordinating adaptive reactions, the brain tries to restore neuroplasticity by increasing S100B levels in persons with DD. However, the compensatory–restorative mechanism and neuroimmune functioning differ in patients with depression; therefore, some researchers report elevated S100B levels in patients with Affective Disorders [ 34 , 35 , 36 ]. Other authors show a decrease or no difference in the content of the S100B protein in the blood serum and in the cerebrospinal fluid of patients with Affective and Anxiety Disorders compared to mentally healthy individuals [ 19 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… [24] In clinical studies, the S100B level was found to be elevated in the serum and cerebrospinal fluid of patients with major depressive disorder. [25] , [26] Real-time in vivo two-photon microscopy revealed that depression model mice had significant leakage of a 40-kDa fluorophore-conjugated dextran into the perivascular region, implying a loss of BBB integrity. [27] Inflammatory factors were shown to cross the BBB and induce depression in polycystic ovary syndrome.…”
Section: Sepsis Causes Depression-like Behavior By Disrupting the Bbbmentioning
confidence: 99%